Examining the Impact of QuickReads' Technology and Print Formats on Fluency, Comprehension, and Vocabulary Development for Elementary Students. (3rd October 2016) - Trainin, Guy; Hayden, H. Emily; Wilson, Kathleen; Erickson, Joan
ABSTRACT: National reports reveal one third of American fourth graders read below basic level on measures of comprehension. One critical component of comprehension is fluency: rapid, accurate, expressive reading with automaticity and prosody. Many fluency studies and classroom interventions focus only on reading rate, but this alone is not sufficient. This experimental study focused on QuickReads, which uses science and social studies texts to build reading fluency, vocabulary, and comprehension. We explored the impact of QuickReads in print-only and print + technology formats for 1, 484 students in second through fifth grades. Using hierarchical linear modeling with pre–post design, we found significant gains in fluency, comprehension, and vocabulary for students in all grades using either QuickReads format over control. Results generalized across achievement groups, ethnicities, and ELL levels. Implementation measures indicated high teacher fidelity to intervention techniques, lending robustness to student results. This study provides an example of scaling up validated instructional practices and lends support for important elements of fluency instruction: emphasizing prosody as well as rate, including content area topics, supported and independent practice, vocabulary and comprehension development, and motivational aspects such as ease of use.